Differentially expressed microRNAs in colorectal cancer metastasis - Abba, Mohammed (Genom Data, 2015)
Tumor metastasis continues to be the most significant contributor to cancer related mortality, and although several studies have examined expression profiles emanating from patients with metastatic disease, very little information is available about signatures that differentiate metastatic lesions from primary tumors and associated normal tissues, largely because such matched tissue sample series are rare. This study was specifically designed to identify the metastasis relevant microRNAs in colorectal cancer and characterize microRNAs that modulate the metastatic phenotype. Here we describe in detail how the data, deposited in the Gene Expression Omnibus (GEO) with the accession number GSE54088, was generated including the basic analysis as contained in the manuscript published in Cancer Research with the PMID 26069251.